An efficient approach to produce 2, 5‐diformylfuran from 5‐hydroxymethylfurfural using air as oxidant. Issue 12 (16th September 2019) - Jia, Wenlong; Du, Juan; Liu, Huai; Feng, Yunchao; Sun, Yong; Tang, Xing; Zeng, Xianhai; Lin, Lu
Abstract: BACKGROUND: 2, 5‐Diformylfuran (DFF) is a versatile bio‐derived platform chemical. Multiple catalytic systems including homogeneous and heterogeneous catalysts have been studied for the oxidation of 5‐hydroxymethylfurfural (HMF) to DFF, but a more efficient and economical approach to produce DFF via HMF remains to be developed. RESULTS: This study provides a practical approach to oxidizing HMF to DFF using Fe(NO3 )3 /Cu(NO3 )2 as catalysts and air as oxidant with the assistance of K2 S2 O8 . The typical oxidation of HMF to DFF was conducted under conditions of 4 wt% catalyst, 80 °C and 3 h, achieving an excellent DFF yield of over 99%. CONCLUSION: In this oxidation reaction, Fe(NO3 )3 played a crucial catalytic role by the redox cycle of Fe(III) and Fe(II), while Cu(NO3 )2 functioned as a co‐catalyst to promote the redox cycle of Fe(II) and Fe(III) by the redox cycle of Cu(II) and Cu(I) with the assistance of oxygen. Meanwhile, NO2 released from the decomposition of Fe(NO3 )3 during the redox cycle of Fe(II) and Fe(III) also participated in the oxidation of Fe(II) to Fe(III) by the redox cycle of NO2 and NO with the assistance of oxygen. Noteworthily, K2 S2 O8 provided an essential acidity to the oxidation of HMF to DFF through its decomposition product SO3 . All these factors together ensured the efficient conversion of HMF and high selectivity of DFF. © 2019 Society of Chemical Industry